(untitled) (Ciudades, 2017)
The empirical evidence finds a clear link between economic success and the presence of skilled human capital. Determining the size and distribution of the creative class in the Spanish regional capitals at the beginning of the Twenty-first century is the main aim of this paper. Also, the possible relationship between the presence of the creative class and the likely relevance of factors such as tolerance and diversity to attract members of the creative class is under investigation. The findings show a complex and unbalanced distribution of the creative class in regional capitals. Furthermore, similar values of tolerance and diversity do not match one single creative class size and social environmental factors do not always attract and retain the creative class in the Spanish regional capitals.